Penguatan Kapasitas Kewirausahaan Siswa melalui Pelatihan dan Pendampingan Penyusunan Business Plan di SMK Ma’arif Ambarawa - Fuadi, Fauzan; Sari, Selly Puspita; Agustina, Fitria Fertha (Universitas Tanjungpura, 2026)
This community engagement program aimed to strengthen students’ entrepreneurial capacity through training and mentoring in business plan development using the Lean Canvas framework at SMK Ma’arif Ambarawa. The program applied a project-based training and mentoring approach consisting of preparation, interactive sessions on entrepreneurship and Lean Canvas, group-based Lean Canvas drafting, iterative mentoring through feedback and revisions, pitching presentations, and the development of a concise business plan. The evaluation employed pretest–posttest assessments, a Lean Canvas rubric, participant observation, and documentation of outputs. The results indicate improved students’ understanding of entrepreneurship concepts and their ability to design business ideas in a more systematic manner. The most notable improvements were observed in the refinement of customer segments and the unique value proposition, as well as in the strengthening of revenue streams and cost structure, making the business models more realistic. However, key metrics and unfair advantage remained challenging components, although students began to formulate context-appropriate performance indicators and competitive advantages. Overall, Lean Canvas proved to be a practical tool for entrepreneurship learning, and iterative mentoring was a key factor in enhancing the quality of business designs and students’ readiness to develop more feasible business ideas.